The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.stemcr.2020.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell-Derived Human Striatal Progenitors Innervate Striatal Targets and Alleviate Sensorimotor Deficit in a Rat Model of Huntington Disease

Abstract: Huntington disease (HD) is an inherited late-onset neurological disorder characterized by progressive neuronal loss and disruption of cortical and basal ganglia circuits. Cell replacement using human embryonic stem cells may offer the opportunity to repair the damaged circuits and significantly ameliorate disease conditions. Here, we showed that in-vitro-differentiated human striatal progenitors undergo maturation and integrate into host circuits upon intra-striatal transplantation in a rat model of HD. By com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 28 publications
4
42
1
1
Order By: Relevance
“…To date, there have been multiple studies evaluating molecular and cellular mechanisms of abnormal development in HD. For example see recent studies on transcriptomics [4], and studies of induced pluripotent stem cell lines [5][6][7][8][9][10][11][12], as well as studies investigating abnormal brain development in HD animal models [13][14][15][16][17]. As a whole, this literature is rich and supports the notion that abnormal development may play a role in the pathogenesis of disease.…”
mentioning
confidence: 73%
“…To date, there have been multiple studies evaluating molecular and cellular mechanisms of abnormal development in HD. For example see recent studies on transcriptomics [4], and studies of induced pluripotent stem cell lines [5][6][7][8][9][10][11][12], as well as studies investigating abnormal brain development in HD animal models [13][14][15][16][17]. As a whole, this literature is rich and supports the notion that abnormal development may play a role in the pathogenesis of disease.…”
mentioning
confidence: 73%
“…Results of cell fate in our HD mouse studies uniquely appear to follow a neuronal developmental path in contrast to a more gliogenic outcome, potentially due to the differentiation potential of the starting material or the transplantation niche (Goldberg et al, 2017; Qian et al, 2020; Yoon et al, 2020). A recent study using a rat model of HD induced by intrastriatal quinolinic acid injection, showed that human embryonic stem cell-derived MSN progenitors differentiate in vitro , undergo maturation, integrate into host circuits, and display properties similar to those of the host striatum 2 months after transplantation (Besusso et al, 2020), suggesting feasibility of transplanting differentiated MSN progenitors. Notably, behavioral studies in this model demonstrated functional recovery of some impaired sensorimotor responses but not in more complex behaviors (e.g., rotarod test).…”
Section: Discussionmentioning
confidence: 99%
“…The expression pattern of the DARPP-23 positive cells indicates that they are striatal projection neurons of the type normally generated by the lateral ganglionic eminence (LGE). This is further supported by their ability to establish axonal connections with downstream striatal targets, including globus pallidus and substantia nigra, accompanied by a gradual improvement in measures of sensorimotor performance on the side opposite to the excitotoxic lesion and transplantation (Ma et al, 2012;Adil et al, 2018;Besusso et al, 2020). Although the extent and functionality of the graft-derived connectivity need to be explored in greater detail, the recent study by Besusso et al (2020), using a combination of immunohistochemistry and monosynaptic rabies virus tracing, has provided initial evidence that the hESC-derived striatal grafts can become well integrated into the lesioned host striatal circuitry.…”
Section: Generation Of Midbrain Da and Striatal Projection Neurons Frmentioning
confidence: 92%
“…The percentage of DARPP-32+/CTIP2+ neurons generated in these protocols vary between 20 and 60%. Also, the grafts have been shown to contain other neuronal types, including GABAergic interneurons (Besusso et al, 2020), and in one case also a significant component (27%) of GFAP-positive astrocytes (Adil et al, 2018).…”
Section: Generation Of Midbrain Da and Striatal Projection Neurons Frmentioning
confidence: 99%